Bacterial and human proteomes dataset - Borgmästars, Emmy; Enroth, Stefan; Lindberg, Julia Hedlund; Sundfeldt, Karin; Gyllensten, Ulf (Uppsala University, 2025)
The dataset consists of a fasta file including 36 bacterial species and the human proteome obtained from the Uniprot database. The 36 bacterial species were chosen based on ≥ 1 % detection of total reads in 16S sequencing data of dried cervicovaginal fluid from paper cards. This dataset can be used as a reference file for quantification of bacterial proteins using maxquant.

The fasta file contains a representative proteome for the following species:

Proteome_ID

Species

UP000234775

Aerococcus christensenii

UP000016519

Alloscardovia omnicolens

UP000005984

Anaerococcus lactolyticus

UP000003191

Bifidobacterium breve

UP000003503

Dialister micraerophilus

UP000005947

Fannyhessea vaginae

UP000005392

Fusobacterium animalis

UP000002521

Fusobacterium nucleatum

UP000258888

Gardnerella vaginalis

UP000255264

Haemophilus pittmaniae

UP000004115

Lactobacillus iners

UP000003242

Megasphaera lornae

UP000002631

Mycoplasma hominis

UP000004206

Peptostreptococcus anaerobius

UP000002786

Prevotella bivia

UP000033103

Sneathia vaginalis

UP000000423

Ureaplasma parvum

UP000029628

Veillonella montpellierensis

UP000003744

Anaerococcus tetradius

UP000253807

Haemophilus parainfluenzae

UP000067598

Lactobacillus crispatus

UP000189488

Lactobacillus gasseri

UP000327236

Lactobacillus jensenii

UP000318911

Lactobacillus mulieris

UP000070160

Megasphaera hutchinsoni

UP000070531

Prevotella amnii

UP000254072

Prevotella disiens

UP001254699

Sneathia sanguinegens

UP000238573

Streptococcus anginosus

UP000008693

Bifidobacterium dentium

UP000005388

Streptococcus urinalis

UP000189488

Lactobacillus gasseri

UP000000821

Streptococcus agalactiae

UP000000625

Escherichia coli

UP000008816

Staphylococcus aureus

UP000000431

Chlamydia trachomatis

UP000005640

Homo sapiens
Keywords: Other health sciences not elsewhere classified; Microbiology not elsewhere classified; Proteomics and metabolomics; Translational and applied bioinformatics; Medical and Health Sciences; Medicin och hälsovetenskap; Microbiology; Mikrobiologi; Other Health Sciences; Annan hälsovetenskap